THE INFLUENCE OF PRODUCT ATTRIBUTES, SATISFACTION, AND WORD OF MOUTH ON BIOFORMA PURCHASE DECISIONS IN PONTIANAK CITY - Hery Medianto Kurniawan (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2022)
The research aims to determine the effect of product attributes, staisfaction and Word of Mouth on Biopharmaceutical Purchasing Decisions in Pontianak City. This form of research uses associative research methods or causal designs. This research was conducted in Pontianak City and was conducted for 2 (two) months, namely October - November 2022. In this study, there were 100 respondents, where the selected respondents were consumers of biopharmaceuticals in accordance with the main characteristics of the population that had been determined in the study. Measurement of research data using a Likert Scale. Data analysis uses Multiple Linear Regression, where before data analysis is carried out, Instrument Tests and Classical Assumption Tests are carried out first. The results of the research based on simultaneous tests (goodness of fit) can be concluded that product attribute variables, sataisfaction and word of mouth have a significant effect on biopharmaceutical purchasing decisions in Pontianak City. The results of the partial analysis show that the product attribute variables and word of mouth have a significant effect on the purchasing decisions of biopharmaceuticals in Pontianak City and are significant for the satisfaction and have no significant effect on the purchasing decisions of biopharmaceuticals in Pontianak City. Keywords : Product attribute, Staisfaction, Word of Mouth, Purchase Decision